Different outcomes after kidney transplantation between African Americans and Whites: A matter of income? A single‐center study. Issue 11 (21st October 2019) - Arvelakis, Antonios; Lerner, Susan; Wadhera, Vikram; Delaney, Veronica; Ames, Scott; Benvenisty, Alan; Sehgal, Vinita; Bhansali, Arjun; De Boccardo, Graciela; Sun, Eric; Florman, Sander; Shapiro, Ron
Abstract: Background: Our center has one of the largest representations of African Americans in listed and transplanted patients. We investigated if and how racial differences affect outcomes in our patient population. Methods: We performed a retrospective analysis of all kidney transplants in African American and (non‐Hispanic) White patients in our center from 1/1/2005 to 12/31/2014. Cox regression was performed to evaluate the adjusted hazard ratios for graft loss. We investigated the influence of socioeconomic status on transplant outcomes. We stratified our patients into three groups based on income: lower (<$50 000 annual household income), medium ($50 000‐100 000 annual household income), and higher (>$100 000 annual household income. Results: There were 1333 patients in our study, 696 Whites and 637 African Americans. The 1‐, 5‐, and 10‐year graft survival between the two groups was 96.5% vs 91.1%, 89% vs 80.7%, and 77% vs 66.3%, respectively ( P  < .001 by Log Rank, Breslow and Taron‐Ware). When we compared the two groups separately in each income category, we found no statistical difference between African Americans and Whites in graft survival. In the regression model, income and not race was the significant factor influencing graft survival ( P  < .001 vs P  = .61).